Analysis of the Economic Independence of Islamic Boarding Schools Through Smart Card Digitalization Innovation (Case Study of Al-Amin Islamic Boarding School Mojokerto) - Syarifuddin, Muhammad; Toha, Mohammad; Hamza, Hichem (Malacca: Journal of Management and Business Development, 2024)
In making economic growth almost all aspects are supported by the sophistication of information technology which is developing very rapidly. The government has made many policies to continue to spur economic growth. The economic independence of Islamic boarding schools through the advancement of digital technology at the Al-Amin Islamic Boarding School, in addition to being a place to gain knowledge, is also taught how students can become good entrepreneurs. In its implementation, it applies an entrepreneurial spirit and technological advances by innovating to support the needs of students and providing a method of student entrepreneurship based on technology and entrepreneurs that can be applied in the lives of its students. This study uses a type of field research with a qualitative approach. Data collection techniques used through observation, interviews, documentation, online data searches. The results of this study are that the economic independence of Islamic boarding schools at the Al-Amin Sooko Islamic Boarding School is implemented in the form of businesses and learning that can increase the economic independence of Islamic boarding schools. Several professional businesses such as Al Amin Mart, financing business units, refill water depots, sewing training. So that the Al-Amin Islamic Boarding School can develop both economically and also produce alumni who are able to become entrepreneurs who can benefit the community. In addition, the Al-Amin Islamic Boarding School has an innovation in economic digitalization by having a smart card. The purpose of this innovation is so that students can use it safely and comfortably, where cash is prone to the risk of being lost and so on. In the efforts made by the Al-Amin Islamic Boarding School, it can be said to be independent even though not entirely.